A high bending resistance ceramic material for 5G communication base station and its preparation method

The anti-bending sintering aid was prepared by blending calcining, and the polyacrylamide/levodopamine film was covered on the surface of the ceramic sintered powder. The sintered powder was coated with HA crystals, which solved the problem that the ceramic material had too large grains during high-temperature sintering, which caused the ceramic material to have too large grains during the high-temperature sintering process. The problem of strength reduction has achieved the preparation of high bending and low dielectric constant ceramic materials.

CN118930228BActive Publication Date: 2025-02-14XINHUA COUNTY SHUNDA ELECTRONIC CERAMICS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411436217.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-15
Publication Date
2025-02-14
Estimated Expiration
2044-10-15

AI Technical Summary

Technical Problem

Existing low-dielectric constant ceramic materials are prone to form too large grains during high-temperature sintering, resulting in a decrease in material strength. The dielectric performance of commonly used low-temperature co-solvent sintering additives is poor, affecting the density and dielectric properties of the material.

Method used

The anti-bending sintering aid is prepared by blending and calcining of Li2CO3, SiO2, Bi2O3 and Al2O3, and the surface of the sintered powder is covered with polyacrylamide/levodopamine film, and the sintered powder is coated with HA crystals to control grain growth and improve the material Density and bending resistance.

Benefits of technology

It significantly improves the bending and dielectric properties of ceramic materials, avoids the decline in material strength caused by excessive grains, and improves the density and dielectric properties of the materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118930228B_ABST
    Figure CN118930228B_ABST
Patent Text Reader

Abstract

The present invention relates to the field of ceramic materials, specifically a high bending resistance ceramic material for 5G communication base stations and a preparation method thereof. The steps include: calcination preparation of bending resistance sintering aids; preparation of HA-coated ceramic sintering powder; composite and column sintering of ceramic particles. The present invention uses polyacrylamide / L-dopamine membrane as an organic template to induce HA mineralization, which ensures that the HA crystal forms an ordered structure, so that the crystal obtains good mechanical properties, effectively reduces the problem of porosity in ceramics caused by grain growth, and improves the density of ceramics. In addition, some pores and cracks are inevitably generated in the ceramic green body during the sintering process. When the finished ceramic is subjected to an external load, the cracks will continue to expand. At this time, the HA crystals and cracks meet to consume the energy of the external load, thereby enhancing the strength of the ceramic and greatly improving the bending resistance of the ceramic material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of ceramic materials, and in particular to a high-bending-resistance ceramic material for 5G communication base stations and a preparation method thereof. Background Art

[0002] The rapid development of 5G communication technology is placing higher demands on the core materials used in communication base stations. 5G base stations need to handle higher-frequency signals and transmit larger data capacities, while also requiring smaller size, higher reliability, and longer service life. Against this backdrop, high-εr microwave materials, which limit electromagnetic wave energy transmission, and printed circuit boards (PCBs) and metals, which exhibit significant losses, are no longer the preferred materials for driving mobile communication technology toward higher frequencies. Microwave dielectric ceramics with high Q·f and low dielectric constants are attracting significant attention and research. When used as substrates, these materials can effectively increase signal transmission rates and significantly reduce signal energy loss in the microwave and millimeter wave bands.

[0003] Common low dielectric constant materials include silicates, phosphates, aluminates and borates. These ceramic materials often require high-temperature sintering, which can easily cause the ceramic grains to be too large, resulting in a serious decrease in the strength of the ceramic material. Even if the sintering temperature can be lowered by adding low-temperature eutectic sintering aids, most low-temperature eutectic sintering aids have poor dielectric properties and are prone to mutual repulsion with the ceramic material, which not only affects the strength of the ceramic, but also causes a decrease in dielectric properties. Summary of the Invention

[0004] In order to solve the above technical defects, the present invention has developed a high-bending-resistant ceramic material for 5G communication base stations with low dielectric constant, high quality factor and high bending resistance, and a preparation method thereof.

[0005] A method for preparing a high-bending-resistance ceramic material for a 5G communication base station, comprising the following steps:

[0006] S1: Calcination preparation of bending-resistant sintering aid

[0007] Li2CO3, SiO2, Bi2O3 and Al2O3 are mixed and ball-milled to obtain a mixed slurry, which is then dried, ground and sieved to obtain a mixed fine powder, which is then calcined in a muffle furnace and rapidly annealed, ground and sieved to obtain a bending-resistant sintering aid;

[0008] S2: Preparation of HA-coated ceramic sintered powder

[0009] B2O3, CaCO3, anhydrous ethanol and zirconium oxide balls are placed in a ball mill and milled, and the mixture is sieved and then sintered at high temperature to obtain a sintered powder. A tris(hydroxymethyl)aminomethane aqueous solution is placed in a container, and polyacrylamide and L-dopamine are added after adjusting the pH. The mixture is stirred and ultrasonically treated to obtain a coating solution. The sintered powder is immersed in the coating solution, filtered and dried to obtain a film-coated sintered powder. The film-coated sintered powder is then immersed in a CaCl2 buffer solution, washed, immersed in a Na2HPO4 buffer solution, washed again, immersed in sodium lauryl sulfate, and taken out and air-dried to obtain a HA grain-coated sintered powder.

[0010] S3: Composite and column sintering of ceramic particles

[0011] Ta2O5 and Sr(NO3)2 are placed in a container, cyclohexane is added, and the mixture is sealed, heated, and then filtered to obtain SrTa2O6. HA grain-coated sintered powder, SrTa2O6, and BaTi4O9 are weighed, and SrTa2O6 and BaTi4O9 are first mixed and ball-milled to obtain a dielectric performance enhancing material. The weighed HA grain-coated sintered powder and the dielectric performance enhancing material are placed in a mortar, and then a bending-resistant sintering aid and polyvinyl alcohol are added and ground. Ceramic particles are obtained after sieving. The ceramic particles are pressed into a column and first sintered at low temperature and then sintered at high temperature. After cooling, a high-bending-resistant and low-dielectric-constant ceramic material is obtained.

[0012] Furthermore, step S1 of calcining the anti-bending sintering aid comprises the following steps:

[0013] S1.1: Li2CO3, SiO2, Bi2O3, and Al2O3 were placed in a ball mill, and an equal amount of deionized water was added and ball milled for 3-4 hours at a speed of 250-300 rpm to obtain a mixed slurry. The mixed slurry was dried and then ground, and passed through a 100-120 mesh sieve to obtain a mixed fine powder;

[0014] S1.2: calcining the mixed fine powder in a muffle furnace at 1200-1300°C for 4-4.5 hours, taking it out and quickly annealing it in cold water, grinding it and passing it through a 100-120 mesh sieve to obtain a bending-resistant sintering aid.

[0015] Furthermore, step S2 of preparing HA-coated ceramic sintered powder comprises the following steps:

[0016] S2.1: Weigh B2O3 and CaCO3 raw materials at a molar ratio of 1:(2.4-2.6), mix them, add anhydrous ethanol and zirconium oxide balls at a mass ratio of 1:(1-1.5):(2-2.5), and add them to a ball mill. Adjust the speed to 250-300 rpm and ball mill for 6-8 hours. After passing through an 80-100 mesh sieve, place the mixture in a muffle furnace and heat it to 1000-1100°C at a heating rate of 5-6°C / min. Maintain the temperature and sinter for 8-10 hours to obtain a sintered powder.

[0017] S2.2: 80-100 parts by mass of an aqueous solution of 8-10 g / L tris(hydroxymethyl)aminomethane was placed in a container and the pH was adjusted to 8-8.5. Then, 0.1-0.3 parts by mass of polyacrylamide and 0.2-0.3 parts by mass of levodopamine were added. After stirring for 30-35 minutes, ultrasonic treatment was performed at an ultrasonic frequency of 20-25 kHz for 50-60 minutes to obtain a coating solution. The sintered powder was immersed in the coating solution for 25-30 minutes, and then filtered and dried to obtain a coated sintered powder.

[0018] S2.3: Immerse the coated sintered powder in CaCl2 buffer for 20-25 minutes, rinse with deionized water 1-2 times, and then immerse it in Na2HPO4 buffer. Let it stand for 20-25 minutes, rinse with deionized water 1-2 times, and then immerse it in sodium dodecyl sulfate. Let it stand at room temperature for 1-1.5 hours, and then air-dry to obtain HA grain-coated sintered powder.

[0019] Furthermore, step S3 of compounding and sintering ceramic particles into pressed columns includes the following steps:

[0020] S3.1: Mix Ta2O5 and Sr(NO3)2 in a molar ratio of 1:(1-1.2) in a container, then add 15-20 times the mass of cyclohexane. Seal the container and heat to 400-450°C for 1-1.5 hours. Filter to obtain SrTa2O6.

[0021] S3.2: Weigh HA grain-coated sintered powder, SrTa2O6, and BaTi4O9 in a mass ratio of 1:(0.02-0.03):(0.02-0.03), place the weighed SrTa2O6 and BaTi4O9 in a ball mill, add 1.5-2 times the mass of anhydrous ethanol and 2.5-3 times the mass of zirconia balls with a diameter of 2-3 mm, and ball mill at a ball milling speed of 250-300 rpm for 4-5 hours to obtain a dielectric performance enhancing material, place the weighed HA grain-coated sintered powder and the dielectric performance enhancing material in a mortar, add 2-3wt% of a bending resistance sintering aid and 18-20wt% of polyvinyl alcohol, grind until uniform spherical small particles are formed, and pass through a 95-100 mesh sieve to obtain ceramic particles;

[0022] S3.3: Place the ceramic particles in a pressing mold, use a tablet press to apply a pressure of 8-10 MPa, maintain for 30-40 seconds to obtain a columnar ceramic green body, place the columnar ceramic green body in a box-type resistance furnace and heat it to 500-600°C at a heating rate of 1-1.5°C / min, then place it in a muffle furnace and heat it to 780-800°C at a heating rate of 4-5°C / min, keep warm for 6-8 hours, and naturally cool in the furnace to obtain a high-bending-strength and low-dielectric-constant ceramic material.

[0023] Furthermore, in step S1.1, the molar ratio of Li2CO3, SiO2, Bi2O3 and Al2O3 is 1:1:1:(0.2-0.3).

[0024] Furthermore, the zirconia balls in step 2.1 are composed of zirconia balls with a diameter of 6 mm and zirconia balls with a diameter of 3 mm in a mass ratio of 1:(0.4-0.6).

[0025] Furthermore, the method for adjusting the pH in step S2.2 is to add a hydrochloric acid solution.

[0026] Furthermore, in step S2.3, the concentration of the CaCl2 buffer solution is 55-60 g / L, the pH is 7.5-8, and the concentration of the Na2HPO4 buffer solution is 35-40 g / L, the pH is 8.5-9.

[0027] Furthermore, the columnar ceramic green body in step S3.3 has a height of 6-8 mm and a diameter of 10-12 mm.

[0028] A high-bending-resistance ceramic material for a 5G communication base station is prepared by the above-mentioned method for preparing a high-bending-resistance ceramic material for a 5G communication base station.

[0029] The beneficial effects are: 1. The present invention first grinds B2O3 and CaCO3 together and then sinters to obtain a sintered powder. At this time, a Ca3(BO3)2 main crystal phase is initially formed in the sintered powder, which determines the formation direction of the main crystal phase in the subsequent sintering process. Then, a layer of polyacrylamide / levodopamine film is covered on the surface of the sintered powder as an organic template for subsequent induction of HA mineralization, ensuring that the subsequent HA crystals form an ordered structure and obtain good mechanical properties. In the subsequent sintering process, the HA crystals can not only play a pinning role at the grain boundaries, inhibit grain boundary movement, and prevent the growth of Ca3(BO3)2 ceramic grains, but also effectively reduce the problem of porosity in ceramics caused by grain growth, thereby improving the density of the ceramics. Moreover, since some pores and cracks are inevitably generated in the ceramic green body during the sintering process, when the finished ceramic is subjected to an external load, the cracks will continue to expand. When encountering HA crystals with good mechanical properties, they can consume the energy of the external load, thereby enhancing the strength of the ceramics. In summary, the bending resistance of the ceramic material is greatly improved.

[0030] 2. The present invention first prepares SrTa2O6 by Ta2O5 and Sr(NO3)2, and then mixes and ball-mills it with BaTi4O9 to obtain a dielectric performance enhancement material. When the HA grain-coated sintered powder is first sintered at low temperature and then sintered at high temperature, the low temperature sintering first discharges the polyacrylamide and L-dopamine in the HA grain-coated sintered powder and the polyvinyl alcohol in the ceramic particles, and then sintered at high temperature to make the Sr with similar ionic radius and lattice energy 2+ 、Ba 2+ and Ca 2+ They can be doped and replaced with each other without causing distortion of the lattice structure, thereby greatly reducing the repulsion of SrTa2O6 and BaTi4O9 from the main crystal phase of Ca3(BO3)2 during high-temperature sintering. The bending resistance of the resulting ceramic material will not only not decrease, but also improve the dielectric properties of the ceramic material because SrTa2O6 and BaTi4O9 themselves have excellent dielectric properties.

[0031] 3. The present invention prepares a bending-resistant sintering aid by blending and calcining Li2CO3, SiO2, Bi2O3 and Al2O3. The Li2CO3 decomposes to generate Li2O during the sintering process, which can form a low eutectic with SiO2 and Bi2O3. These low eutectics have a low melting point, which helps to reduce the overall temperature of subsequent sintering, thereby reducing excessive grain growth and thermal stress of the ceramic material. In addition, high-strength Al2O3 particles are added as a reinforcing phase. During the subsequent calcination process, the liquid phase generated by Bi2O3 and Li2O can be filled into the gaps between the grains, thereby improving the density and strength of the ceramic material, thereby further enhancing the bending strength of the ceramic material. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 This is a flow chart of the method for preparing high-bending-resistant ceramic materials for 5G communication base stations used in an embodiment of the present invention. DETAILED DESCRIPTION

[0033] The following will clearly and completely describe the technical solutions in the embodiments of the present invention in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of the present invention.

[0034] Example 1: A high-bending ceramic material for 5G communication base stations and a preparation method thereof, such as Figure 1 As shown, the following steps are included:

[0035] S1: Calcination preparation of bending-resistant sintering aid

[0036] S1.1: Li2CO3, SiO2, Bi2O3, and Al2O3 were placed in a ball mill at a molar ratio of 1:1:1:0.2. An equal amount of deionized water was added and the mixture was ball milled for 3 hours at 250 rpm to obtain a mixed slurry. The mixed slurry was dried and ground, and passed through a 100-mesh sieve to obtain a mixed fine powder.

[0037] S1.2: The mixed fine powder is placed in a muffle furnace and calcined at 1200°C for 4 hours. After being taken out, it is quickly put into cold water for annealing. After grinding, it is passed through a 100-mesh sieve to obtain a bending-resistant sintering aid.

[0038] S2: Preparation of HA-coated ceramic sintered powder

[0039] S2.1: Weigh B2O3 and CaCO3 raw materials in a molar ratio of 1:2.4, mix them, add them to anhydrous ethanol and zirconia balls in a mass ratio of 1:1:2, and add them to a ball mill, wherein the zirconia balls are composed of zirconia balls with a diameter of 6 mm and zirconia balls with a diameter of 3 mm in a mass ratio of 1:(0.4-0.6). Adjust the speed to 250 rpm and ball mill for 6 hours. After passing through an 80-mesh sieve, place the mixture in a muffle furnace and heat it at a heating rate of 5°C / min to 1000°C. Maintain the temperature and sinter for 8 hours to obtain a sintered powder;

[0040] S2.2: 80 parts by mass of an 8 g / L aqueous solution of tris(hydroxymethyl)aminomethane was placed in a container, and hydrochloric acid solution was added to adjust the pH to 8. Then, 0.1 parts by mass of polyacrylamide and 0.2 parts by mass of levodopamine were added. After stirring for 30 minutes, ultrasonic treatment was performed at an ultrasonic frequency of 20 kHz for 50 minutes to obtain a coating solution. The sintered powder was immersed in the coating solution for 25 minutes, and then filtered and dried to obtain a coated sintered powder.

[0041] S2.3: Immerse the coated sintered powder in a CaCl2 buffer solution with a concentration of 55 g / L and a pH of 7.5 for 20 minutes, rinse it once with deionized water, and then immerse it in a Na2HPO4 buffer solution with a concentration of 35 g / L and a pH of 8.5. After standing for 20 minutes, rinse it once with deionized water, and then immerse it in sodium dodecyl sulfate. Let it stand at room temperature for 1 hour, and then air-dry to obtain HA grain-coated sintered powder.

[0042] S3: Composite and column sintering of ceramic particles

[0043] S3.1: Mix Ta2O5 and Sr(NO3)2 in a 1:1 molar ratio in a container, then add 15 times the mass of cyclohexane. Seal the container and heat to 400°C for 1 hour. Filter to obtain SrTa2O6.

[0044] S3.2: Weigh HA grain-coated sintered powder, SrTa2O6, and BaTi4O9 in a mass ratio of 1:0.02:0.02, place the weighed SrTa2O6 and BaTi4O9 in a ball mill, add 1.5 times the mass of anhydrous ethanol and 2.5 times the mass of zirconia balls with a diameter of 2 mm, and ball mill at a ball milling speed of 250 rpm for 4 hours to obtain a dielectric performance enhancement material, place the weighed HA grain-coated sintered powder and the dielectric performance enhancement material in a mortar, add 2wt% of a bending resistance sintering aid and 18wt% of polyvinyl alcohol, grind until uniform spherical small particles are formed, and pass through a 95-mesh sieve to obtain ceramic particles;

[0045] S3.3: Place the ceramic particles in a pressing mold, use a tablet press to apply a pressure of 8 MPa, and maintain for 30 seconds to obtain a columnar ceramic green body with a height of 6 mm and a diameter of 10 mm. Place the columnar ceramic green body in a box-type resistance furnace and heat it to 500°C at a heating rate of 1°C / min, then place it in a muffle furnace and heat it to 780°C at a heating rate of 4°C / min, keep warm for 6 hours, and naturally cool in the furnace to obtain a high-bending-strength and low-dielectric-constant ceramic material.

[0046] Example 2: A high-bending ceramic material for 5G communication base stations and a preparation method thereof, such as Figure 1 As shown, the following steps are included:

[0047] S1: Calcination preparation of bending-resistant sintering aid

[0048] S1.1: Li2CO3, SiO2, Bi2O3, and Al2O3 were placed in a ball mill at a molar ratio of 1:1:1:0.3. An equal amount of deionized water was added and the mixture was ball milled for 3 hours at 250 rpm to obtain a mixed slurry. The mixed slurry was dried and ground, and passed through a 100-mesh sieve to obtain a mixed fine powder.

[0049] S1.2: The mixed fine powder is placed in a muffle furnace and calcined at 1200°C for 4 hours. After being taken out, it is quickly put into cold water for annealing. After grinding, it is passed through a 100-mesh sieve to obtain a bending-resistant sintering aid.

[0050] S2: Preparation of HA-coated ceramic sintered powder

[0051] S2.1: Weigh B2O3 and CaCO3 raw materials in a molar ratio of 1:2.6, mix them, add them to anhydrous ethanol and zirconia balls in a mass ratio of 1:1.5:2.5, and add them to a ball mill, wherein the zirconia balls are composed of zirconia balls with a diameter of 6 mm and zirconia balls with a diameter of 3 mm in a mass ratio of 1:(0.4-0.6). Adjust the speed to 250 rpm and ball mill for 6 hours. After passing through an 80-mesh sieve, place the mixture in a muffle furnace and heat it at a heating rate of 5°C / min to 1000°C. Maintain the temperature and sinter for 8 hours to obtain a sintered powder;

[0052] S2.2: 100 parts by mass of an 8 g / L aqueous solution of tris(hydroxymethyl)aminomethane was placed in a container, and hydrochloric acid solution was added to adjust the pH to 8. Then, 0.3 parts by mass of polyacrylamide and 0.3 parts by mass of levodopamine were added. After stirring for 30 minutes, ultrasonic treatment was performed at an ultrasonic frequency of 20 kHz for 50 minutes to obtain a coating solution. The sintered powder was immersed in the coating solution for 25 minutes, and then filtered and dried to obtain a coated sintered powder.

[0053] S2.3: Immerse the coated sintered powder in a CaCl2 buffer solution with a concentration of 55 g / L and a pH of 7.5 for 20 minutes, rinse it once with deionized water, and then immerse it in a Na2HPO4 buffer solution with a concentration of 35 g / L and a pH of 8.5. After standing for 20 minutes, rinse it once with deionized water, and then immerse it in sodium dodecyl sulfate. Let it stand at room temperature for 1 hour, and then air-dry to obtain HA grain-coated sintered powder.

[0054] S3: Composite and column sintering of ceramic particles

[0055] S3.1: Mix Ta2O5 and Sr(NO3)2 in a molar ratio of 1:1.2 in a container, then add 20 times the mass of cyclohexane. Seal the container and heat to 400°C for 1 hour. Filter to obtain SrTa2O6.

[0056] S3.2: Weigh HA grain-coated sintered powder, SrTa2O6, and BaTi4O9 in a mass ratio of 1:0.03:0.03, place the weighed SrTa2O6 and BaTi4O9 in a ball mill, add 2 times the mass of anhydrous ethanol and 3 times the mass of zirconia balls with a diameter of 2 mm, and ball mill at a ball milling speed of 250 rpm for 4 hours to obtain a dielectric performance enhancement material, place the weighed HA grain-coated sintered powder and dielectric performance enhancement material in a mortar, add 3wt% of a bending resistance sintering aid and 20wt% of polyvinyl alcohol, grind until uniform spherical small particles are formed, and pass through a 95-mesh sieve to obtain ceramic particles;

[0057] S3.3: Place the ceramic particles in a pressing mold, use a tablet press to apply a pressure of 8 MPa, and maintain for 30 seconds to obtain a columnar ceramic green body with a height of 6 mm and a diameter of 10 mm. Place the columnar ceramic green body in a box-type resistance furnace and heat it to 500°C at a heating rate of 1°C / min, then place it in a muffle furnace and heat it to 780°C at a heating rate of 4°C / min, keep warm for 6 hours, and naturally cool in the furnace to obtain a high-bending-strength and low-dielectric-constant ceramic material.

[0058] Example 3: A high-bending ceramic material for 5G communication base stations and a preparation method thereof, such as Figure 1 As shown, the following steps are included:

[0059] S1: Calcination preparation of bending-resistant sintering aid

[0060] S1.1: Li2CO3, SiO2, Bi2O3, and Al2O3 were placed in a ball mill at a molar ratio of 1:1:1:0.2. An equal amount of deionized water was added and the mixture was ball milled for 4 hours at 300 rpm to obtain a mixed slurry. The mixed slurry was dried and ground, and passed through a 120-mesh sieve to obtain a mixed fine powder.

[0061] S1.2: calcining the mixed fine powder in a muffle furnace at 1300°C for 4.5 hours, taking it out and quickly annealing it in cold water, grinding it and passing it through a 120-mesh sieve to obtain a bending-resistant sintering aid.

[0062] S2: Preparation of HA-coated ceramic sintered powder

[0063] S2.1: Weigh B2O3 and CaCO3 raw materials in a molar ratio of 1:2.4, mix them, add them to anhydrous ethanol and zirconia balls in a mass ratio of 1:1:2, and add them to a ball mill, where the zirconia balls are composed of zirconia balls with a diameter of 6 mm and zirconia balls with a diameter of 3 mm in a mass ratio of 1:(0.4-0.6). Adjust the speed to 300 rpm and ball mill for 8 hours. After passing through a 100-mesh sieve, place the mixture in a muffle furnace and heat it to 1100°C at a heating rate of 6°C / min. Maintain the temperature and sinter for 10 hours to obtain a sintered powder;

[0064] S2.2: 80 parts by mass of a 10 g / L tris(hydroxymethyl)aminomethane aqueous solution was placed in a container, and hydrochloric acid solution was added to adjust the pH to 8.5. Then, 0.1 parts by mass of polyacrylamide and 0.2 parts by mass of levodopamine were added. After stirring for 35 minutes, ultrasonic treatment was performed at an ultrasonic frequency of 25 kHz for 60 minutes to obtain a coating solution. The sintered powder was immersed in the coating solution for 30 minutes, and then filtered and dried to obtain a coated sintered powder.

[0065] S2.3: Immerse the coated sintered powder in a CaCl2 buffer solution with a concentration of 60 g / L and a pH of 8 for 25 minutes, rinse it twice with deionized water, and then immerse it in a Na2HPO4 buffer solution with a concentration of 40 g / L and a pH of 9. After standing for 25 minutes, rinse it twice with deionized water, and then immerse it in sodium dodecyl sulfate. Let it stand at room temperature for 1.5 hours, and then air-dry to obtain HA grain-coated sintered powder.

[0066] S3: Composite and column sintering of ceramic particles

[0067] S3.1: Mix Ta2O5 and Sr(NO3)2 in a 1:1 molar ratio in a container, then add 15 times the mass of cyclohexane, seal the container, and heat to 450°C for 1.5 hours. Filter to obtain SrTa2O6.

[0068] S3.2: Weigh HA grain-coated sintered powder, SrTa2O6, and BaTi4O9 in a mass ratio of 1:0.02:0.02, place the weighed SrTa2O6 and BaTi4O9 in a ball mill, add 1.5 times the mass of anhydrous ethanol and 2.5 times the mass of zirconia balls with a diameter of 3 mm, and ball mill at a ball milling speed of 300 rpm for 5 hours to obtain a dielectric performance enhancing material, place the weighed HA grain-coated sintered powder and the dielectric performance enhancing material in a mortar, add 2wt% of an anti-bending sintering aid and 18wt% of polyvinyl alcohol, grind until uniform spherical small particles are formed, and pass through a 100-mesh sieve to obtain ceramic particles;

[0069] S3.3: Place the ceramic particles in a pressing mold, use a tablet press to apply a pressure of 10 MPa, and maintain for 40 seconds to obtain a columnar ceramic green body with a height of 8 mm and a diameter of 12 mm. Place the columnar ceramic green body in a box-type resistance furnace and heat it to 600°C at a heating rate of 1.5°C / min, then place it in a muffle furnace and heat it to 800°C at a heating rate of 5°C / min, keep warm for 8 hours, and naturally cool it in the furnace to obtain a high-bending-strength and low-dielectric-constant ceramic material.

[0070] Comparative Example 1: The difference between Comparative Example 1 and Example 1 is that Comparative Example 1 removes step S2.2 and step S2.3, and replaces the subsequent HA grain-coated sintered powder with sintered powder. The remaining steps are the same as Example 1.

[0071] Comparative Example 2: The difference between Comparative Example 2 and Example 1 is that Comparative Example 2 does not prepare dielectric performance enhancing materials with SrTa2O6 and BaTi4O9 in step S3.2, and does not add dielectric performance enhancing materials for blending and sintering. The remaining steps are the same as Example 1, and a ceramic material is finally obtained, which is recorded as Comparative Example 2.

[0072] Comparative Example 3: The difference between Comparative Example 3 and Example 1 is that Comparative Example 3 removes step S1 and does not add anti-bending sintering aid in step S3.2. The remaining steps are the same as Example 1. Finally, a ceramic material is obtained, which is recorded as Comparative Example 3.

[0073] Experiment 1: Take the high-bending and low-dielectric constant ceramic materials prepared in Examples 1-3, Comparative Example 1, Comparative Example 2, and Comparative Example 3, and take three portions respectively. The flexural strength of each is tested using the method in the national standard "GBT6569-2006". The data are recorded and tabulated. As shown in Table 1, it can be seen that the flexural strength of the high-bending and low-dielectric constant ceramic materials prepared in Examples 1-3 is greater than that of Comparative Example 1 and Comparative Example 3. This proves that coating the sintered powder with HA crystals can improve the flexural strength of the ceramic material after sintering. At the same time, it can be proved that the flexural-resistant sintering aid prepared by blending and calcining Li2CO3, SiO2, Bi2O3, and Al2O3 can also be added to the subsequent sintering process to improve the flexural strength of the ceramic material.

[0074] Table 1: Flexural strength of ceramic materials

[0075]

[0076] Experiment 2: Take the high-bending-resistance, low-dielectric-constant ceramic materials prepared in Examples 1-3 and Comparative Example 2, take three portions of each, and use the open cavity resonant cavity method to test and calculate the dielectric constant, record the data and make a table, as shown in Table 2, and then use the closed cavity resonant cavity method to test and calculate the quality factor Q·f value, record the data and make a table, as shown in Table 3. From Tables 1, 2 and 3, it can be seen that the dielectric constants of the high-bending-resistance, low-dielectric-constant ceramic materials prepared in Examples 1-3 are all smaller than that of Comparative Example 2, while the quality factor Q·f values ​​are all greater than that of Comparative Example 2, and the flexural strength is slightly greater than that of Comparative Example 2. It can be proved that the introduction of dielectric performance enhancers made of SrTa2O6 and BaTi4O9 during the ceramic sintering process can improve its dielectric properties without reducing the flexural strength of the ceramic material.

[0077] Table 2: Dielectric constants of ceramic materials

[0078]

[0079] Table 3: Quality factor Q·f value of ceramic materials

[0080]

[0081] The above embodiments are merely illustrative of the principles and effects of the present invention and are not intended to limit the present invention. Anyone skilled in the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by one of ordinary skill in the art without departing from the spirit and technical principles disclosed herein are intended to be covered by the claims of the present invention.

Claims

1. A method for preparing a high bending resistance ceramic material for a 5G communication base station, characterized in that: The following steps are involved: S1: Calcination preparation of bending-resistant sintering aid Li2CO3, SiO2, Bi2O3 and Al2O3 are mixed and ball-milled to obtain a mixed slurry, which is then dried and ground and then sieved to obtain a mixed fine powder, which is then calcined in a muffle furnace and then rapidly annealed, and then ground and sieved to obtain a bending-resistant sintering aid; S2: Preparation of HA-coated ceramic sintered powder B2O3, CaCO3, anhydrous ethanol and zirconium oxide balls are placed in a ball mill for ball milling, and then sintered at high temperature after being sieved to obtain a sintered powder; a tris(hydroxymethyl)aminomethane aqueous solution is placed in a container, polyacrylamide and L-dopamine are added after adjusting the pH, and ultrasonic treatment is performed after stirring to obtain a coating solution; the sintered powder is immersed in the coating solution, filtered and dried to obtain a coated sintered powder; the coated sintered powder is then immersed in a CaCl2 buffer solution, washed and immersed in a Na2HPO4 buffer solution, washed again and immersed in sodium dodecyl sulfate, taken out and air-dried to obtain a HA grain-coated sintered powder; S3: Composite and sintering of ceramic particles Ta2O5 and Sr(NO3)2 are placed in a container, cyclohexane is added, and the container is sealed and heated before filtering to obtain SrTa2O6. HA grain-coated sintered powder, SrTa2O6 and BaTi4O9 are weighed, SrTa2O6 and BaTi4O9 are first mixed and ball-milled to obtain a dielectric performance enhancing material, the weighed HA grain-coated sintered powder and the dielectric performance enhancing material are placed in a mortar, and then a bending resistance sintering aid and polyvinyl alcohol are added for grinding, and ceramic particles are obtained after sieving, and the ceramic particles are pressed into a column and first sintered at a low temperature and then sintered at a high temperature, and then cooled to obtain a high bending resistance and low dielectric constant ceramic material.

2. The method for preparing a high bending resistance ceramic material for a 5G communication base station according to claim 1, characterized in that: Step S1: calcination preparation of bending-resistant sintering aid, comprising the following steps: S1.1: Li2CO3, SiO2, Bi2O3 and Al2O3 are placed in a ball mill, and deionized water of equal mass is added and mixed and ball milled for 3-4 hours. The ball mill speed is set to 250-300rpm to obtain a mixed slurry. The mixed slurry is dried and then ground, and passed through a 100-120 mesh sieve to obtain a mixed fine powder; S1.2: The mixed fine powder is placed in a muffle furnace and calcined at a temperature of 1200-1300°C for 4-4.5 hours. After being taken out, it is quickly put into cold water for annealing. After grinding, it is passed through a 100-120 mesh sieve to obtain a bending-resistant sintering aid.

3. The method for preparing a high bending resistance ceramic material for a 5G communication base station according to claim 2, characterized in that: Step S2 prepares HA-coated ceramic sintered powder, comprising the following steps: S2.1: Weigh B2O3 and CaCO3 raw materials with a molar ratio of 1: (2.4-2.6), mix them with anhydrous ethanol and zirconium oxide balls in a mass ratio of 1: (1-1.5): (2-2.5), add them into a ball mill, adjust the speed to 250-300rpm, ball mill for 6-8 hours, pass through an 80-100 mesh sieve, place in a muffle furnace and heat to 1000-1100℃ at a heating rate of 5-6℃ / min, maintain the temperature and sinter for 8-10 hours to obtain sintered powder; S2.2: 80-100 parts by weight of an aqueous solution of tris(hydroxymethyl)aminomethane with a concentration of 8-10 g / L is placed in a container, the pH is adjusted to 8-8.5, and then 0.1-0.3 parts by weight of polyacrylamide and 0.2-0.3 parts by weight of levodopa are added, and after stirring for 30-35 minutes, ultrasonic treatment is performed at an ultrasonic frequency of 20-25 kHz for 50-60 minutes to obtain a coating solution, and the sintered powder is immersed in the coating solution for 25-30 minutes, and filtered and dried to obtain a coated sintered powder; S2.3: Immerse the coated sintered powder in CaCl2 buffer for 20-25 minutes, rinse with deionized water 1-2 times, immerse in Na2HPO4 buffer, let stand for 20-25 minutes, rinse with deionized water 1-2 times, then immerse in sodium dodecyl sulfate, let stand at room temperature for 1-1.5 hours, and air-dry to obtain HA grain-coated sintered powder.

4. The method for preparing a high bending resistance ceramic material for a 5G communication base station according to claim 3, characterized in that: Step S3, the composite and column pressing sintering of ceramic particles, comprises the following steps: S3.1: Mix Ta2O5 and Sr(NO3)2 in a molar ratio of 1:(1-1.2) in a container, then add 15-20 times the mass of cyclohexane, seal and heat to 400-450℃ for 1-1.5 hours, and filter to obtain SrTa2O6; S3.2: Weigh HA grain-coated sintered powder, SrTa2O6 and BaTi4O9 in a mass ratio of 1: (0.02-0.03): (0.02-0.03), place the weighed SrTa2O6 and BaTi4O9 in a ball mill, add 1.5-2 times the mass of anhydrous ethanol and 2.5-3 times the mass of zirconia balls with a diameter of 2-3 mm, and ball mill at a ball milling speed of 250-300rpm for 4-5 hours to obtain a dielectric performance enhancing material, place the weighed HA grain-coated sintered powder and the dielectric performance enhancing material in a mortar, add 2-3wt% of an anti-bending sintering aid and 18-20wt% of polyvinyl alcohol, grind until uniform spherical small particles are formed, and pass through a 95-100 mesh sieve to obtain ceramic particles; S3.3: Place the ceramic particles in a die, use a tablet press to apply a pressure of 8-10MPa, maintain for 30-40 seconds to obtain a columnar ceramic green body, place the columnar ceramic green body in a box-type resistance furnace and heat it to 500-600℃ at a heating rate of 1-1.5℃ / min, then place it in a muffle furnace and heat it to 780-800℃ at a heating rate of 4-5℃ / min, keep it warm for 6-8 hours, and naturally cool it in the furnace to obtain a high bending resistance and low dielectric constant ceramic material.

5. The method for preparing a high bending resistance ceramic material for a 5G communication base station according to claim 2, characterized in that: The molar ratio of Li2CO3, SiO2, Bi2O3 and Al2O3 in step S1.1 is 1:1:1:(0.2-0.3).

6. The method for preparing a high bending resistance ceramic material for a 5G communication base station according to claim 3, characterized in that: The zirconia balls in step 2.1 are composed of zirconia balls with a diameter of 6 mm and zirconia balls with a diameter of 3 mm in a mass ratio of 1:(0.4-0.6).

7. The method for preparing a high bending resistance ceramic material for a 5G communication base station according to claim 3, characterized in that: The method for adjusting the pH in step S2.2 is to add a hydrochloric acid solution.

8. The method for preparing a high bending resistance ceramic material for a 5G communication base station according to claim 3, characterized in that: In step S2.3, the concentration of the CaCl2 buffer is 55-60 g / L, the pH is 7.5-8, and the concentration of the Na2HPO4 buffer is 35-40 g / L, the pH is 8.5-9.

9. The method for preparing a high bending resistance ceramic material for a 5G communication base station according to claim 4, characterized in that: The columnar ceramic green body in step S3.3 has a height of 6-8 mm and a diameter of 10-12 mm.

10. A high bending resistance ceramic material for a 5G communication base station, characterized in that: The material is prepared by the method for preparing a high bending-resistant ceramic material for a 5G communication base station as described in any one of claims 1 to 9.

Citation Information

Patent Citations

  • Temperature-stable type ultralow-dielectric-constant microwave dielectric ceramic Ca5LaB3O11

    CN104446374A

  • Microwave dielectric ceramic with medium dielectric constant and low loss

    CN104774008A